Axial flux generator with novel flat wire for direct‐drive wind turbines - Gokhan Cakal; Ozan Keysan (IET Renewable Power Generation, 2021)
Abstract With the increased demand for renewable energy resources, the direct‐drive wind turbine generators have been studied intensely in the last few decades. One megawatt direct‐drive axial flux permanent magnet generator is presented. The novelty in this design is that instead of conventional stranded wires, the windings of the generator are manufactured from a conductor sheet by cutting and bending processes. This creates critical advantages of superior current ratings, ease of manufacturing, and reduced structural mass. An optimization study is conducted with the presented fully analytical model, and the optimum design is compared with the other wind power generators presented in the literature. At the end, a 1 MW, 480 kNm, and 16 tons direct‐driven generator is achieved.